Time to return to play and reinjury rate of hamstring injuries with and without intramuscular tendon involvement. A systematic review and meta-analysis - O'Sullivan, M.; Mullins, K.; van der Made, A. D.; Carton, P. (Scientific Journal of Sport and Performance, 2025)
Determine whether intramuscular hamstring tendon (IMT) injury prolongs return to play (RTP) and increases odds of reinjury compared to non-IMT injuries. Systematic Review and Meta-Analysis. Data Sources: PubMed, CINAHL, SPORTDiscus, Cochrane Library and EMBASE. Eligibility Criteria: Studies investigating RTP and reinjury rates in athletes who had a hamstring injury and underwent MRI within 7 days. The PEDRO scale and GRADE approach were used. Eight studies with 527 athletes, were included. Lack of blinding and high heterogeneity meant that the studies included were of fair quality and very low certainty of evidence. IMT injuries had an extended RTP compared to non-IMT injuries (mean difference:16.35 days, 95%CI: 8.51-24.19, p < .001). BAMIC 2c injuries prolonged RTP by 6.0 days compared to 2a & 2b combined (mean difference:6.03 days, 95% CI: 0.03-12.03, p = .05, Z = 1.97). The mean difference between BAMIC 3c and 3a/b injuries was 15 days (95% CI: -1.62-32.91, p = .08). Tendon involvement did not increase the odds of re-injury (OR = 2.98, 95%CI 0.93-9.59, Z = 1.83, p = .07). The overall very low quality of the included studies gravely impacts conclusions that may be drawn regarding comparisons of time to RTP and re-injury rate. IMT injuries may have an extended RTP duration of approximately two weeks compared to non-IMT injury. No between-group differences were found in re-injury rate. To provide accurate prognosis to inform clinical decisions for injuries with and without IMT involvement, high-quality prospective studies with blinding of treating clinicians for MRI findings are paramount.